2015
DOI: 10.1007/s00381-015-2712-8
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric ischemic stroke from an apoplectic prolactinoma

Abstract: In the pediatric population, there is only one other case of pituitary apoplexy presenting with stroke, which was secondary to vasospasm. We present the first case of pituitary apoplexy presenting with stroke secondary to ICA compression. Though rare, it is important to consider that pituitary apoplexy may present with non-classical symptoms such as ischemic stroke even in pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…This is one of the few reports of an acute ischemic stroke occurring secondary to a large pituitary adenoma in a child. Pituitary tumors causing ischemic strokes in a large vascular territory are very rare [5][6][7][8][9], and the majority of reported cases have occurred in the setting of apoplexy. In a recent literature review, Banerjee et al reported a total of 25 cases of cerebral infarction from pituitary apoplexy.…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the few reports of an acute ischemic stroke occurring secondary to a large pituitary adenoma in a child. Pituitary tumors causing ischemic strokes in a large vascular territory are very rare [5][6][7][8][9], and the majority of reported cases have occurred in the setting of apoplexy. In a recent literature review, Banerjee et al reported a total of 25 cases of cerebral infarction from pituitary apoplexy.…”
Section: Discussionmentioning
confidence: 99%
“…3) To the best of our knowledge, only 2 previous pediatric cases of cerebral infarction associated with pituitary tumor apoplexy have been published. 3,4) Herein, we report a rare presentation of ischemic stroke due to apoplexy of pituitary macroadenoma in an adolescent male. The patient provided informed written consent for publishing the case report.…”
Section: Pituitary Apoplexy In An Adolescent Male With Macroprolactin...mentioning
confidence: 95%
“…3,9,14,16,17 Although the vast majority of apoplexy cases concerns adults, there are also a few reports in the pediatric population. 18,19 In gestation, maternal PA can appear at any time [20][21][22] but usually happens perinatally. 23,24 Purpose PA is a rare and potentially life-threatening condition with a highly variable clinical presentation 25,26 that is typically abrupt and impressive.…”
Section: Introduction Definitionmentioning
confidence: 99%